Space Resource Utilization: A View from an Emerging Space Faring Nation (Studies in Space Policy,, 2018)
The book speaks to the need for a regulatory framework with regards to space resource utilization. In doing so, significant elements of the subject matter have been explored, taking into account the different phases of a space mission and the perspectives of the various actors and participants in the space arena. The book tackles the subject matter from a number of angles. An analysis of the current national and international governance frameworks is performed, with regards to resource extraction and utilization in space. The view of established and emerging space nations is analyzed next, specifically with extraction and utilization in mind, and in light of the new United State (US) Commercial Space Launch Competitiveness Act (CSLCA) of 2015. A brief analysis of the various budgets allocated to space exploration is given.